2021
DOI: 10.1017/s0950268821001801
|View full text |Cite
|
Sign up to set email alerts
|

Spatial analysis of the incidence of Dengue, Zika and Chikungunya and socioeconomic determinants in the city of Rio de Janeiro, Brazil

Abstract: In 2015–2016, simultaneous circulation of dengue, Zika and chikungunya in the municipality of Rio de Janeiro (Brazil) was reported. We conducted an ecological study to analyse the spatial distribution of dengue, Zika and chikungunya cases and to investigate socioeconomic factors associated with individual and combined disease incidence in 2015–2016. We then constructed thematic maps and analysed the bivariate global Moran indices. Classical and spatial models were used. A distinct spatial distribution pattern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
14
0
8

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 24 publications
3
14
0
8
Order By: Relevance
“…Although being considered a triple epidemic, we found a higher number of chikungunya cases (102), followed by dengue (23), and no cases of Zika. These results are in agreement with the information that the arbovirus' space-time distribution is different during an epidemic [50,51]. During the peak of the triple epidemic in 2015-2016, the spatial analysis and the incidence of dengue, Zika and chikungunya in the city of RJ showed that only 25% of the studied areas had a high incidence of the three arboviruses [51] and that they have formed disease transmission clusters, with only 31% of them transmitting all three arboviruses simultaneously [50].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although being considered a triple epidemic, we found a higher number of chikungunya cases (102), followed by dengue (23), and no cases of Zika. These results are in agreement with the information that the arbovirus' space-time distribution is different during an epidemic [50,51]. During the peak of the triple epidemic in 2015-2016, the spatial analysis and the incidence of dengue, Zika and chikungunya in the city of RJ showed that only 25% of the studied areas had a high incidence of the three arboviruses [51] and that they have formed disease transmission clusters, with only 31% of them transmitting all three arboviruses simultaneously [50].…”
Section: Discussionsupporting
confidence: 91%
“…These results are in agreement with the information that the arbovirus' space-time distribution is different during an epidemic [50,51]. During the peak of the triple epidemic in 2015-2016, the spatial analysis and the incidence of dengue, Zika and chikungunya in the city of RJ showed that only 25% of the studied areas had a high incidence of the three arboviruses [51] and that they have formed disease transmission clusters, with only 31% of them transmitting all three arboviruses simultaneously [50]. Some explanations for this phenomenon are that there is competition between viruses, especially between CHIKV and ZIKV, both in nature and in the laboratory [52].…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with previous ecological studies [ 33 ], this investigation found that living in areas with better socioeconomic indicators (i.e., improved sanitation and income) and with a higher percentage of self-identified white residents was associated with lower risks of ZIKV infections in pregnancy. The association between socioeconomic indicators and microcephaly aligns with a previous study from the city of Recife, in Northeast Brazil [ 34 ], which found a strong association between the prevalence of microcephaly during the 2015–2016 epidemic and poor living conditions defined by the percentage of household heads with an income below two times minimum wage.…”
Section: Discussionsupporting
confidence: 90%
“…Inadequate water treatment as well as precarious sanitary sewage have been previously related to vector-borne infections [ 33 ]. Those unsatisfactory environmental conditions become more obvious soon after the start of the rainy season, particularly in tropical and subtropical areas, where the prevalence of water puddles can facilitate breeding sites for Aedes spp .…”
Section: Discussionmentioning
confidence: 99%
“…7 The peak of the ZIK outbreak occurred in 2016 (with 8 859 confirmed cases) and since then, its circulation decreased, with 860, 86, 20, and 28 confirmed cases in 2018, 2019, 2020 and 2021, respectively. 8 The effect of continuous DENV circulation in the spread of ZIKV is controversial; on one hand some studies reported a strong correlation between endemic DEN and ZIK incidence, 9,10 and on the other, no geospatial correlation in the distribution of the incidence of both viruses was reported by others. 11 DENV and ZIKV are flaviviruses with high similarities in their structural envelope proteins, 1 which results in frequent induction of cross-reactivity antibody responses.…”
mentioning
confidence: 99%